Storia breve della relazione filosofica tra la bellezza e l’esistenza etica e politica degli esseri umani (Itinera, 2016)
The article analyzes the relationship between the philosophical notion of beauty and the ethical and political life of human beings through the history of Western philosophy, from Plato to contemporary authors.